Предмет: Алгебра,
автор: danil17500
помогите плиз 2 4 6 дам 10 баллов
Приложения:
Ответы
Автор ответа:
1
Здравствуйте!
Вот ваше решение:
(-a+b)(b-a) = (-a+b)^2 = (b-a)^2 = b^2 - 2ab + a^2
(a+b)(-a-b) = -(a+b)(a+b) = -(a+b)^2 = -(a^2 + 2ab + b^2) = -a^2 - 2ab - b^2
(-a-b)(-a-b) = (-a-b)^2 = a^2 + 2ab + b^2
danil17500:
спасибо большое
Похожие вопросы
Предмет: География,
автор: sofiymas200
Предмет: География,
автор: arutunanartur41
Предмет: Литература,
автор: eksanorntmbs
Предмет: Информатика,
автор: Альбина22001
Предмет: Литература,
автор: Аноним